MANIPULATION AS AN INTEGRAL PART OF BUSINESS COMMUNICATION - Шутяк, Ирина; Ткач, Лиля (SWorldJournal, 2020)
The article reviews one of the varieties of social influence on humanity and one of the most interesting types of human behaviour - manipulation, which is undoubtedly an integral part of the social culture of communication. It is very difficult for an un